2014
DOI: 10.1515/cclm-2013-0307
|View full text |Cite
|
Sign up to set email alerts
|

Increased B-type natriuretic peptide levels in early-onset versus late-onset preeclampsia

Abstract: BNP levels were significantly higher in EOP than in LOP patients. The cut-off value <24.5 pg/mL seems to be a powerful discriminative indicator excluding preeclampsia. The amount of proteinuria and total protein levels correlate with the elevation of the BNP levels. In EOP the extent of proteinuria is higher than in the LOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…Seven studies reported on BNP levels,78, 79, 80, 81, 82, 83, 84 of which three were applicable for a meta‐analysis ( Figure 5). 78, 79, 80 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies reported on BNP levels,78, 79, 80, 81, 82, 83, 84 of which three were applicable for a meta‐analysis ( Figure 5). 78, 79, 80 …”
Section: Resultsmentioning
confidence: 99%
“…One study reported on FABP4 levels in pre-eclampsia compared with controls and found statistically higher FABP4 levels in pre-eclampsia vs. non-hypertensive pregnancy. 77 Myocardial failure markers in pre-eclampsia Brain natriuretic peptide and N-terminal pro-BNP Seven studies reported on BNP levels, [78][79][80][81][82][83][84] of which three were applicable for a meta-analysis ( Figure 5). [78][79][80] In all seven studies and in meta-analysis, BNP levels were significantly higher in pre-eclampsia than in controls.…”
Section: Insulin Plasma Glucose and Fatty Acid-binding Proteinmentioning
confidence: 99%
“…Although the actual pathways that may connect this biomarker to heart failure remain unclear, these pathways are somehow related to a concordant pattern of fluctuations with the B‐type natriuretic peptide (BNP) . This latter biomarker has been already implicated in the pathophysiology of preeclampsia …”
Section: Introductionmentioning
confidence: 99%
“…11 This latter biomarker has been already implicated in the pathophysiology of preeclampsia. 12,13 Taking this information together, it is easily assumed that CA-125 could be a promising biomarker that could be used for the detection of preeclampsia. During the last decade several studies investigated this association; however, the presented evidence is conflicting.…”
mentioning
confidence: 99%
“…Vasopressin is synthesized and released together with co-peptine; compared to normal pregnancy, serum concentrations of co-peptine are higher in EPE but not LPE [41], and are already detectable before clinical onset of disease [42]. Similarly, serum concentrations of natriuretic peptides types A, B and C are higher in preeclampsia than in normal pregnancy, which is particularly true for EPE as compared to LPE [43,44,45,46,47].…”
Section: Renal Physiology In Normal Pregnancy and In Two Types Of mentioning
confidence: 99%